The Development of Doby Delivery System using Laravel Framework - Tarmizi, Alya Humaira Syahmi; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2026)
The Doby Delivery System was developed to address inefficiencies in Royal Doby’s manual laundry operations, such as poor data management, limited feedback channels, and scheduling issues. This web-based system streamlines services for customers, drivers, and administrators through features like user registration, order tracking, secure payments, automated alerts, and feedback tools. Built with Laravel (backend), HTML, CSS, JavaScript as a frontend, and MySQL as a database, the system uses a prototype methodology involving planning, prototyping, user feedback, and refinement. Key modules include login, service management, membership, communication, delivery tracking, and payment. A case study approach with stakeholder input ensured the system met specific needs. User Acceptance Testing showed a 92% satisfaction rate, indicating strong approval and effective problem-solving. Future enhancements may include predictive analytics for personalized services and system scaling to support more users. Additionally, the technology significantly enhanced administrative efficiency and data accuracy, and future suggestions include the incorporation of mobile applications for increased accessibility and scalability for wider institutional use.